Enhancing IP service provision over heterogeneous wirelessnetworks a path toward 4G. - Becchetti, L. (IEEE Communications magazine)
Second-generation mobile radio systems have been deployed successfully worldwide and have evolved to higher data rates and services. Third-generation mobile radio systems are currently starting to be developed in different regions of the world. Today, the open question is how the third-generation systems will evolve. It is very likely that fourth-generation systems will not be a single standardized air interface, but a set of different technologies and standards. In particular, wireless LAN/wireless PAN type systems are designed for high/medium-data-rate access, low range, and, in general, low mobility. They are applicable to corporate networks and public access as a complement to cellular mobile radio systems for hot spot applications such as airports, hotels, and campuses. In this specific WLAN/WPAN framework and to guarantee an agreed QoS provision over such infrastructures, we propose a solution based on the wireless adaptation layer approach. In particular, aspects related to wireless link impairments and traffic requirements are approached by the implementation of configurable, modular software that is adapted to the specific conditions and needs of the particular wireless infrastructures